Unveiling blazar synchrotron emission: A multiwavelength polarimetric study of high-synchrotron and low-synchrotron peaked populations - Capecchiacci, Sara; Liodakis, Ioannis; Middei, Riccardo; Kim, Dawoon E.; Di Gesu, Laura; Agudo, Iván; Agís-González, Beatriz; Arbet-Engels, Axel; Blinov, Dmitry; Chen, Chien Ting; Ehlert, Steven R.; Gau, Ephraim; et al. (Astronomy & Astrophysics, 2025)
The polarimetric properties of blazars enable us to place constraints on the acceleration mechanisms that fuel their powerful jets. By studying the multiwavelength polarimetric behaviour of high-synchrotron peaked (HSP) and low-synchrotron peaked (LSP) blazars, we aim to explore differences in their emission mechanisms and magnetic field structure in the acceleration region. In this study, we take advantage of several X-ray polarisation observations of HSP by the IXPE, including four new observations of Mrk 501, along with optical polarisation observations of LSP from RoboPol and other instruments. We find that the polarisation degree (PD) distribution of HSP in X-rays is systematically higher than in optical and mm-radio wavelengths, as reported in previous IXPE publications. The distribution of the X-ray electric vector position angles (PA) is centred around the jet axis with most of the observations consistent with zero difference within uncertainties. In fact, the distribution of the offset of the PA from the jet axis is consistent between the LSP and HSP populations (with PA measured in optical for the first, X-ray for the latter), suggesting a common magnetic field structure close to the acceleration region. These results offer strong support for the emerging energy stratified scenario of particle acceleration followed by energy loss in blazar jets.
CRIS-Team Scopus Importer:2025-11-28
Keywords: BL Lacertae objects: general; Galaxies: active; Galaxies: jets; Galaxy: nucleus; Techniques: polarimetric